1990
DOI: 10.1099/0022-1317-71-5-1215
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bovine Herpesvirus Type 1 Glycoprotein gI in Transfected Bovine Cells Induces Spontaneous Cell Fusion

Abstract: Bovine MDBK cells were transfected with Rous sarcoma virus-based vectors for constitutive expression of the bovine herpesvirus type 1 (BHV-1) glycoprotein, gI. Cell lines stably expressing recombinant gI were cloned and characterized. Recombinant gI was localized intracellularly, predominantly in a perinuclear region, and on the cell surface. Cells expressing gI exhibited spontaneous polykaryon formation, thus confirming the fusogenic activity described previously in gI-expressing transfected murine LMTK-cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…The fusion function ofgI may be species-specific as the gI gene used in our studies was the same as that used by Fitzpatrick et al, 1988b) when they observed polykaryon formation in gl-expressing murine cells.…”
Section: Short Communicationmentioning
confidence: 94%
“…The fusion function ofgI may be species-specific as the gI gene used in our studies was the same as that used by Fitzpatrick et al, 1988b) when they observed polykaryon formation in gl-expressing murine cells.…”
Section: Short Communicationmentioning
confidence: 94%
“…When HSVgB is expressed in mammalian cells it causes considerable cell membrane fusion resulting in syncytium formation (Ali et al, 1987). BHVgB expressed in mammalian cells also displays similar membranefusing abilities (Fitzpatrick et al, 1988). In recombinant pseudodiploid HSV which expresses both glycoproteins, BHVgB can complement an essential function of HSVgB which has been blocked by a neutralizing monoclonal antibody (MAb) H233 (Misra & Blewett, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…gB is the most conserved glycoprotein, with its function as a fusion protein well documented for several of the herpesviruses (10,19,38,48,51,52).…”
mentioning
confidence: 99%